Implementasi Kurikulum Merdeka terhadap Pola Pikir Guru Mata Pelajaran Bahasa Indonesia Kelas VII di SMP Negeri 2 Sakra Barat - Hadi, Irwan Yon (FONDATIA, 2024)
The Ministry of Education and Culture created the Independent Curriculum to provide schools the freedom to explore their capabilities in accordance with the infrastructure and resources at their disposal. In order to maximize the results, the autonomous curriculum also gives teachers greater latitude in how they present the curriculum and gives students more opportunity to reach their full potential. The following goals guided the conduct of this study: 1) To ascertain how the independent curriculum is being implemented in relation to the mindset of the class VII Indonesian language teachers at SMP Negeri 2 Sakra Barat, 2) To ascertain the difficulties that subject teachers encounter when attempting to apply the independent curriculum to the mindset of the class VII students at SMP Negeri 2 Sakra Barat. Qualitative descriptive research is what this kind of study is. Techniques for gathering data include documentation, interviews, and observation. The principal, teachers, and students of SMP Negeri 2 Sakra Barat served as the study's subjects. As demonstrated by the implementation of activities relating to the independent curriculum and teacher training, as well as the establishment of the independent curriculum as a permanent curriculum at State Junior High School 2 Sakra Barat for classes VII and VIII, the study's findings show that the school has successfully implemented the independent curriculum.